Pathogenic Enterobacteria in Lemurs Associated With Anthropogenic Disturbance - BUBLITZ, DEANNA C. (Am J Primatol, 2014)
As human population density continues to increase exponentially, speeding the reduction and fragmentation of primate habitat, greater human-primate contact is inevitable, making higher rates of pathogen transmission likely. Anthropogenic effects are particularly evident in Madagascar, where a diversity of endemic lemur species are threatened by rapid habitat loss. Despite these risks, knowledge of how anthropogenic activities affect lemur exposure to pathogens is limited. To improve our understanding of this interplay, we non-invasively examined six species of wild lemurs in Ranomafana National Park for enteric bacterial pathogens commonly associated with diarrheal disease in human populations in Madagascar. Patterns of infection with Enterotoxigenic Escherichia coli, Shigella spp., Salmonella enterica, Vibrio cholerae, and Yersinia spp. (enterocolitica and pseudotuberculosis) were compared between lemurs inhabiting intact forest and lemurs inhabiting degraded habitat with frequent exposure to tourism and other human activity. Fecal samples acquired from humans, livestock, and rodents living near the degraded habitat were also screened for these bacteria. Remarkably, only lemurs living in disturbed areas of the park tested positive for these pathogens. Moreover, all of these pathogens were present in the human, livestock, and/or rodent populations. These data suggest that lemurs residing in forests altered or frequented by people, livestock, or peridomestic rodents, are at risk for infection by these diarrhea-causing enterobacteria and other similarly transmitted pathogens.